Developing a prototype for integrated dental and diabetes care: understanding needs and priorities. (22nd November 2020) - McGowan, K; Phillips, T; Gielis, E; Dover, T; Mitchell, G; Mutch, A; Sexton, C; Sowa, PM; Ivanovski, S
Abstract: Background: Periodontal treatment may be a useful adjunct to medical management of diabetes; however, oral health has not been integrated into multidisciplinary diabetes care in Australia. This study aimed to understand the needs of patients and staff at a diabetes clinic to inform a prototype of integrated dental and diabetes care. Methods: Quantitative and qualitative data were collected from patients and staff at West Moreton Diabetes Clinic (WMDC) between September‐October 2019. Clinical information, survey responses and dental screening results were analysed for 41 patients. Semi‐structured interviews were held with six patients and a focus group with seven staff. Results: Most patients (83%) had not seen a dentist in the previous year. Of the 37 patients with remaining natural teeth, 84% required periodontal assessment and 46% had multiple carious lesions. Unmet treatment needs and rates of access were similar for private and public dental patients. Staff and patients reported high levels of support for incorporation of dental care at WMDC. Conclusions: Integrating oral health into diabetes management is well‐supported by patients and staff to address significant unmet dental needs for both public and private dental patients. Incorporating dental screening/services within diabetes clinics may increase uptake and improve awareness of its importance in diabetes management.